2017
DOI: 10.1210/jc.2016-3153
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated Regulation Among Progesterone, Prostaglandins, and EGF-Like Factors in Human Ovulatory Follicles

Abstract: Context:In animal models, the luteinizing hormone surge increases progesterone (P4) and progesterone receptor (PGR), prostaglandins (PTGs), and epidermal growth factor (EGF)–like factors that play essential roles in ovulation. However, little is known about the expression, regulation, and function of these key ovulatory mediators in humans.Objective:To determine when and how these key ovulatory mediators are induced after the luteinizing hormone surge in human ovaries.Design and Participants:Timed periovulator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 40 publications
3
44
0
Order By: Relevance
“…A total of 60 gene sets were enriched in upregulated genes and 223 gene sets were enriched in downregulated genes at FDR q-value < 0.05. The size of the node corresponds to the number of genes in each gene set enhance PTGS2 (also upregulated in our MII-CC cohort) via EGF to increase prostaglandin production and maintenance of chromosomal spindles [33,[54][55][56]. In addition, AREG mediates hCG-induced STAR expression (also upregulated in our MII-CC cohort), which plays a key role in steroid and progesterone production in human granulosa cells [57], and is a potential predictive biomarker for nuclear maturation [58] and oocyte quality [33].…”
Section: Discussionmentioning
confidence: 99%
“…A total of 60 gene sets were enriched in upregulated genes and 223 gene sets were enriched in downregulated genes at FDR q-value < 0.05. The size of the node corresponds to the number of genes in each gene set enhance PTGS2 (also upregulated in our MII-CC cohort) via EGF to increase prostaglandin production and maintenance of chromosomal spindles [33,[54][55][56]. In addition, AREG mediates hCG-induced STAR expression (also upregulated in our MII-CC cohort), which plays a key role in steroid and progesterone production in human granulosa cells [57], and is a potential predictive biomarker for nuclear maturation [58] and oocyte quality [33].…”
Section: Discussionmentioning
confidence: 99%
“…The hCG-and PGRdependent organic anion transporter, Slco2a1, contributes to prostaglandin synthesis and action in granulosa cells of ovulatory follicles in humans. 49,50 The zinc transporter, Slc39a14, is expressed in cumulus granulosa cells (CGCs) and is thought to regulate free intracellular zinc in mouse oocytes. 51 Direct analysis of the amino acid transporter, Slc7a11, has primarily been limited to regulation of intracellular glutathione synthesis in neuronal tissue, but could play a similar role in FSH-and LH-dependent glutathione production in granulosa cells to support oocyte health.…”
Section: Ir-cko Mice Demonstrate Misregulation Of Gene Involved In mentioning
confidence: 99%
“…Previously, we identified the key role of ATF4 in modulating the expression of COX2 in hGCs (Figure 2B ). Consistently, hCG could also induce COX2 expression ( 18 , 19 ). The increases in COX2 and PGE2 levels are representative indicators of ovulation ( 36 , 37 ).…”
Section: Discussionmentioning
confidence: 59%
“…Cyclooxygenase-2 (COX2) is the key enzyme responsible for the conversion of arachidonic acid into prostaglandins, among which prostaglandin E2 (PGE2) plays important role in multiple physiological and pathological events. hCG can induce COX2 expression and PGE2 production ( 18 , 19 ). It was reported that COX2-deficient mice were susceptible to reproductive malfunction, such as ovulation disorder, decreased fertilization rate, and embryo implantation dysfunction.…”
Section: Introductionmentioning
confidence: 99%